Composition control in biphasic silicate microspheres on stimulating new bone regeneration and repair of osteoporotic femoral bone defect. Issue 2 (29th April 2019) - Ghamor‐Amegavi, Edem P.; Yang, Xianyan; Qiu, Jiandi; Xie, Lijun; Pan, Zhijun; Wang, Juncheng; Zhang, Xiangfeng; Ke, Xiurong; Zhao, Tengfei; Zhang, Lei; Gou, Zhongru
Abstract: Application of bioactive materials as synthetic bone graft substitutes in regenerative medicine has seen great evolution over the past decades in treating challengeable bone defects. However, balancing the preparation conditions and biological performances of inorganic biomaterials remain a great challenge, especially when there is lack of biomaterial design on how to control component distribution and how pathological bone responds to the biomaterial stimulations and osteogenesis. Here, our objective is to develop yolk‐shell Ca‐silicate microspheres and to investigate the potential biological performances to overcome the limitations in repair of osteoporotic bone defects. The introduction of β‐calcium silicate (CaSiO3 ) or mesoporous bioactive glass (MBG) into self‐curing β‐dicalcium silicate (Ca2 SiO4 ) cement shell to form spherical granules (CaSiO3 @Ca2 SiO4, MBG@Ca2 SiO4 ) was to retain the physicochemical property and/or microstructure of each component for optimizing bioactive ion release that could maximize osteostimulation in osteoporosis. We report a scalable shape‐controlled mild fabrication protocol to yield the yolk‐shell granules, endowing to different phases in yolk layer and interconnected macropore networks in the closely packed granule scaffolds. This unique heterostructure preparation is governed by coaxially aligned bilayer nozzle, inorganic powders and biocompatible binders. Extensive in vitro and in vivo evaluation showed that the CaSiO3 @Ca2 SiO4 and MBG@Ca2 SiO4 granules exhibited many superior properties such as controllable ion release, improved biodegradation and enhanced osteogenic capability in comparison with the pure Ca2 SiO4 @Ca2 SiO4, thereby opening new mild‐condition approach in fabricating osteogenesis‐tailored silicate biomaterials for bone regenerative medicine, especially for efficient reconstruction of challenging pathological bone defects.